Uma análise sobre como um grupo de professores de ciências e matemática compreende o papel da intuição e da criatividade em suas práticas docentes - Samuel, Lucius Rafael Sichonany (2014)
The research aims to investigate how a group of science and mathematics teachers understand the role of intuition and creativity in their teaching practices. In the more specific context, sought to examine whether reported by the group in their testimonies methodologies have the potential to foster the intuitive and creative thinking of students as well as enabling rebuild a praxis based on the concept of freedom, using the theoretical assumption philosophical work proposed by Henri Bergson. From a corpus built with material obtained from interviews with nine science and mathematics teachers and subsequent analysis, using the methodology of Discourse Textual Analysis, four categories emerged: Souvenirs and perceptions of the science and mathematics teachers , Intuition and teacher practices, Teacher freedom and practices, Teacher creativity and practices. The research identified that most teachers realize the investigated aspects of intuition and creativity in their educational activities. However, they showed, in their speeches, directive significantly perspectives in their classroom practices. The teachers surveyed associated the intuition to knowledge unmediated, in direct connection with sensitivity and in opposition to the intelligence and rationality. In addition, it allowed heed to the fact that one, emerging from new concepts for time and space and guided by values centered subject, ethics could help rebuild of a new mentality for schools and teachers.